IDENTIFIKASI POTENSI BAHAYA MENGGUNAKAN METODE HAZOP TERMODIFIKASI DI PT. KAYU MEBEL INDONESIA - Handani, Alexander Bryan Christian; Hadi, Yuswono; Putrianto, Novenda Kartika (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
One type of industry that is developing very rapidly among various types of industry in Indonesia is the furniture industry, one of which is PT. Kayu Furniture Indonesia which produces doors. In the door leaf production process, there are 7 machines used, namely double planer, rip, cut, molding, single end, drill and press assembly machines.  The steps in identifying hazards using the HAZOP method begin with knowing the door leaf production flow, namely receiving raw material, leveling the surface of the wood, printing the width of the wood, printing the length of the wood, leveling the sides of the wood material, making profile shapes, making holes in the wood, assembly process. , inspection process. Then proceed with Hazard and Risk Identification in each production process so that the level of danger posed can be known. Seeing the extreme risks that have been described, recommendations that can be given are using PPE in the form of safety gloves, face protection helmets, and carrying out maintenance on machines and making visual displays to remind workers to always use PPE as well as creating good work procedures and conducting K3 training for workers. employees in a comprehensive and sustainable manner.